Jidong Restless Legs Syndrome Cohort Study: Objectives, Design, and Baseline Screening - Wang, Shu-Hong; Chen, Xue-Yu; Wang, Xiao-Ping (Frontiers in Neurology, 2021)
Background: Restless legs syndrome (RLS) is a common neurological disorder with unpleasant leg sensations and serious negative effects on mental and physical health. Many observational studies showed that people with RLS had a high risk of vascular diseases, including cerebrovascular and cardiovascular diseases, but the findings were conflicting. The Jidong RLS Cohort Study is a prospective cohort study designed to mainly examine whether or not RLS is associated with an increased risk of cardiovascular diseases. Methods and design: The study recruited 8,867 healthy participants older than 18 years from October 2014 to December 2015. Participants received a physical examination in the Staff Hospital, Jidong Oilfield Branch, China National Petroleum Corporation. Baseline data and blood samples were collected. RLS was assessed using the international RLS diagnostic criteria. All of subjects would be followed up until December 2025. Major cardiovascular/cerebrovascular events including cardiac death, myocardial infarction, ischemic heart disease, heart failure, atrial fibrillation, ischemic and hemorrhagic stroke will be the primary outcomes. Secondary outcomes include all-cause mortality, the decline in quality of life, cognitive impairment, and depression. Discussion: This study will contribute to the scientific evidence on the association between RLS and cardiovascular risks and also provide an unprecedented opportunity for early detection and prevention of cardiovascular diseases.